B14 Huntingtin mediates anxiety/depression-related behaviours in mouse through BDNF transport and hippocampal neurogenesis. (29th August 2012) - Ben M'Barek, K; Orvoen, S; Pla, P; Benstaali, C; Godin, J; Gardier, A; Saudou, F; David, D; Humbert, S
Abstract : Huntington disease (HD) is associated with early psychiatric symptoms including anxiety and depression. Here, we demonstrate that wild-type huntingtin, the protein mutated in HD, modulates anxiety/depression-related behaviours through its phosphorylation at serines 1181 and 1201, two cyclin-dependent kinase 5 phosphorylation sites. Indeed, genetic phospho-ablation at serines 1181 and 1201 in mouse reduces basal levels of anxiety/depression-like behaviours in mouse. These behavioural effects directly depend on increased adult hippocampal neurogenesis. Indeed, focal dentate gyrus irradiation impaired neurogenesis but also anxiety/depression-related behaviour. Finally, the state of phosphorylation of huntingtin regulates neurogenesis as it influences brain-derived neurotrophic factor transport and subsequent signalling. DD and SH are both equal last authors.